A car-based portable atom gravimeter and its application in field gravity survey - Jiong-Yang Zhang (AIP Publishing LLC, 2021)
As a novel instrument for measuring absolute gravity, the atom gravimeter has shown high sensitivity and stability in the past three decades. In this work, we report a car-based portable atom gravimeter whose sensitivity is at the level of 1.9mGal/Hz (1 Gal = 0.01 m/s2) both for lab and outdoor measurements. Its resolution can reach 30 μGal within an integration time of 10 000 s when located in a quiet place. During four months of gravity observation, there is no drift for the measurement result, showing that this car-based gravimeter has a competitive advantage at long term stability. By using this car-based atom gravimeter in the open air, the field gravity measurements with sub-mGal performance have been demonstrated in the mountain gravity survey. According to the gravity measurement results from our car-based atom gravimeter, the density distribution of this mountain is inverted, which is consistent with the result from the geological exploration.